Alfred Marshall's Theory of Value - Frisch, Ragnar; Marshall, Alfred (Quarterly Journal of Economics, 1950)
I. The various orders of change, 496. — II. Normal equilibrium with reference to short periods, 499. — III. Normal equilibrium with reference to long periods, 507. — IV. The relationship between short period normal and long period normal equilibrium, 519.